Taxes to digital business in Mexico (Revista de Investigaciones Universidad del Quindío, 2021)
Tax collection is the pillar of public spending, which affects the execution of programs for the development of the country without the creation of new taxes, in accordance with this, in September 2019, was presented within the Package Fiscal 2020 the proposal to regularize the collection of value-added tax on products and services marketed online.In recent years, this type of trade has grown exponentially, representing 4.6% of Mexico’s gross domestic product, the tax referred to was already provided under our legislation, however, it was not Effectively regularized, the tax package proposal includes taxing services and goods, that is, platforms such as UBER, NETFLIX, UBER EATS, as well as those that offer lodging services in Mexico, are subject to the tax indicated. The purpose of this investigation is to determine the benefits and cons with respect to the aforementioned proposal, through the review of similar taxes in other countries, in order to analyze the behavior and contrast with the reform of said tax
Keywords: Legislative reform; Tax package; taxation; online commerce